2000
DOI: 10.1029/1999gl003706
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the high‐latitude reconnection site for steady northward IMF

Abstract: The stability of the high-latitude reconnection site under steady northward Interplanetary Magnetic Field (IMF) conditions was investigated using observations in the Earth's magnetospheric cusp. Using proton distributions with characteristic low-energy cutoffs, the distance to the high-latitude reconnection site was monitored during four cusp crossings that had relatively steady solar wind dynamic pressure and IMF clock angle. For these four events, the reconnection site location remained approximately fixed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
162
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 102 publications
(170 citation statements)
references
References 12 publications
5
162
3
Order By: Relevance
“…The plane of the two-dimensional cut contains the magnetic field direction (y-axis) and the axis perpendicular to the Sun- Earth line. Three-dimensional flux measurements from the TIMAS instrument within ±45°of this plane are rotated into the plane by preserving total energy and pitch angle to produce the distribution shown in Figure 2a [see also Fuselier et al, 2000].…”
Section: Observationsmentioning
confidence: 99%
See 3 more Smart Citations
“…The plane of the two-dimensional cut contains the magnetic field direction (y-axis) and the axis perpendicular to the Sun- Earth line. Three-dimensional flux measurements from the TIMAS instrument within ±45°of this plane are rotated into the plane by preserving total energy and pitch angle to produce the distribution shown in Figure 2a [see also Fuselier et al, 2000].…”
Section: Observationsmentioning
confidence: 99%
“…This outflow distribution is seen in the energy-time spectrogram in Figure 1 at energies below 300 eV in the region of interest. The low-velocity cutoffs in Figure 2 needed for the distance calculation are defined at the lowerspeed side of the precipitating and mirrored ion beams where the flux is 1/e lower than the peak flux [see also Fuselier et al, 2000;Trattner et al, 2005]. To ensure a clear reproducible identification of the low-velocity cutoffs, especially for the mirrored distribution embedded within ionospheric outflow distribution, former magnetopause boundary layer distributions and high-velocity magnetosheath ions injected onto the field line while it was already convecting, the precipitating and mirrored ion peaks are fit with Gaussian distributions (blue curves in Figure 2) that are subsequently used to define the 1/e reduced flux location.…”
Section: Observationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although previous studies have demonstrated that enhanced amounts of plasma enter to form a relatively thick, lowlatitude boundary layer 2,12,13 and a denser plasma sheet 13,14 when the IMF is northward even during quiet times, the dominant mechanism of solar wind entry into the magnetosphere (and entry location on the magnetopause) under these conditions is less clear and still controversial. It is still not very clearly understood whether the entering plasma is a result of the highlatitude MR 12,[15][16][17][18][19][20][21][22] , impulsive penetration 23,24 , or from the low latitudes through instabilities 25,26 or gradient drift 27 .…”
mentioning
confidence: 99%